Operation Victory - De Guingand, Francis (London Hodder and Stoughton, 1950)
Marshal Montgomery's Chief of Staff records his experiences from a visit to France and Germany in 1937 through World War.
Include Maps,Conclusions and Index
Keywords: World War (1939-1945) -- Personal Narratives, English